Autonomic computing system: Threats, security issues and an efficient approach for self protection. (2023) - Jain, Vaibhav; Chitra,; Batra, Neera; Marriappan, Jasmine; Kaithal, Parveen Kumar
Abstract: Autonomic computing frameworks are the self overseeing frameworks as indicated by the objectives outlined by the administrator of the system. Incorporation of new elements in framework supported by Autonomic Computing happens as simple as in human body a new cell recreates itself. Autonomic Computing Systems (ACS) are relied upon to accomplish an indistinguishable level of self-direction and inescapability from human autonomic frameworks. Due to the highlights of ACS, the customary security model cannot be connected to ACS any more. The objective of our exploration is to build up a setting based security model and engineering for ACS. Our attention is on self-security highlight of ACS. The self- assurance include is implemented through security settings that we characterize. By considering security settings, security arrangements would dynamic is able to change so as to adapt to new condition.